Private provision of public goods: Do individual climate protection efforts depend on perceptions of climate policy? - Joachim Schleich; Claudia Schwirplies; Andreas Ziegler (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
This paper extends the economic literature on the private provision of public goods by examining the relevance of perceptions of climate policy to voluntary contributions to the public good of climate protection. Based on an analytical model which allows for perceptions of climate policy such as justification of international climate policy, procedural trust and procedural justice to affect voluntary climate protection activities, we examined data from representative surveys among citizens in the USA and Germany. Our microeconometric analysis confirmed the prediction that the perceived justification of international climate policy is positively related to voluntary contributions to climate protection in both countries. We also found empirical support (mainly for the USA) that higher perceived procedural justice lowers citizens' propensity to adopt climate protection activities. In contrast, we found no support that higher perceived procedural trust reduces citizens' propensity to adopt such measures. In a broad interpretation, our empirical results imply that individuals' perceptions about the process of providing public goods should also be considered when analyzing the factors explaining voluntary individual contribution to public goods.
Keywords: H41; Q54; Q58; 330; Public good; voluntary contribution; perceptions of international climate policy; climate protection activities